Code-Switching in the Daily Conversations of Female Students at Pondok Pesantren Nuruttauhid Bulukumba, South Sulawesi: A Sociolinguistic Study - Wahyuni, Sri; Thamrin, M Husni (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2024)
This study aims to analyze the types of code-switching and the factors that cause code-switching in the daily conversations of female students at Pondok Pesantren Nuruttauhid Bulukumba, South Sulawesi. Data were collected from the conversations of 20 female students during the 2021/2022 academic year using observation, interviews, and documentation methods. This research adopts a qualitative approach with a case study method. The results show the use of elements of Arabic, Indonesian, Bugis, and Konjo languages in the students' conversations. The forms of code-switching found include words, word repetition, phrases, and clauses. The factors causing code-switching include the use of Indonesian and regional languages in conversations, changes in situations from formal to informal, limitations in Arabic vocabulary mastery, and the tendency to communicate more quickly and practically. These findings contribute to sociolinguistic studies, particularly in the context of multilingual pesantren-based education.